Safeguarding our seas: tge Calayo Center for Marine Sciences Research and Development - Cueco, Danielle N.
With the continuous discovery of marine resources in the West Philippine Sea and Verde Island Passage Marine Corridor comes its potential exploitation too, and thus the need to conserve and protect it. To do so, the Philippines must strengthen its marine science research prowess while utilizing the ideals of modern research. The Calayo Center for Marine Sciences Research and Development therefore aims to be multi-disciplinary shore-based marine research complex that shall act as a research arm of various stakeholders -- such as government agencies and academes. It shall be located on the western coast of Nasugbu, Batangas, a jump point between to the two crucial bodies of water. The Calayo Center for Marine Sciences Research and Development is designed such that it will depict modern research as a "culture of communication" through juxtaposition of architectural elements.